Cerrado e Ameaças as Pontecialidade: Caracterização etnobotânica da vegetação remanescente do município de Goiandira (GO) - (:unkn) unknown (Universidade Federal de Goiás, 2011)
The study about the Cerrado and its potentials aims to contribute to the increase of information about Cerrado vegetation by understanding the appropriation of nature, knowing this way, the relationship that exists between man and vegetation through the ethnobotanical survey of areas affected in part by PCH - Goiandira. The research methodology was initially based on literature review, then the first step on the field, we present a survey of the vegetation on the properties included in the study area, in a second step, the area was visited, referenced by GPS, and plotted on maps. Residents and owners were interviewed. Interviews were also conducted with urban residents of Goiandira, which can promote comparisons about the vegetation knowledge. The indications ethnobotanics for use according to scientific literature were more significant than any popular indication, which shows that there are many species that can be used for various purposes, such as: medical, ornamental plants for urban forestry, handicrafts, plants, honey, fruit, staining properties among others, which could therefore be used without being removed from the area. But many of these utilities are not known by the human, and plant species are eventually included in deforestation, because they
Cerrado e Ameaças as Pontecialidade: Caracterização etnobotânica da vegetação remanescente do município de Goiandira (GO)
Cerrado and the Potential Threats: ethnobotany characterization of remnant vegetation in the muncipality of Goiandira (GO)
Keywords: utilidades das plantas; espécies vegetais; preservação da biodiversidade.; plants utilities; plant species; preservation of biodiversity.; 1. Utilidades-plantas 2. Espécies vegetais 3. Preservação-biodiversidade 4. Preservação vegetação- Município de Goiandira (GO); CNPQ::CIENCIAS HUMANAS::GEOGRAFIA